S‐doped 3D porous carbons derived from potassium thioacetate activation strategy for zinc‐ion hybrid supercapacitor applications. (7th September 2020) - Wang, Dewei; Wang, Shuangyu; Lu, Zeming
Summary: Aqueous zinc‐ion hybrid supercapacitors (ZHSCs) emerge as a promising option for green energy storage in recent years. However, development of reliable carbon‐based cathodes remains a challenge. Herein, an effective potassium thioacetate activation technique has been promoted for the producing of S‐doped 3D porous carbons (S‐3DPCs) by employing sustainable pine needles as the carbon source without any additives. Different from the previously reported routes, the potassium thioacetate can serve as the activator as well as the S source. The resulting S‐3DPCs display a unique 3D architecture with a large specific surface area, a certain amount of sulfur (~0.88‐3.60 at%), which enables S‐3DPCs to exhibit excellent electrochemical performance as the cathodes for ZHSCs. Particularly, S‐3DPC‐800 (pyrolysis at 800) can deliver a large specific capacity of 203.3 mAh g −1 (the volumetric capacity is 123.8 mAh cm −3 ) in 2 M ZnSO4 at 0.2 A g −1, high rate performance, and outstanding cyclic durability. Moreover, S‐3DPC‐800‐based ZHSCs can possess the maximum energy density up to 162.6 Wh kg −1 (99.0 Wh L −1 ) at a power density of 160 W kg −1 (97.4 W L −1 ), which suggests the significant potential of S‐3DPCs as the robust cathodes for ZHSCs. This facile potassium thioacetate activation strategy points toward a new way to develop S‐doped 3D porous carbon cathodes for high performances ZHSCs applications. Abstract : An effective potassium thioacetate activation strategy has been developed for the producing of S‐doped 3D porous carbons and were used as the cathodes for aqueous zinc‐ion hybrid supercapacitors with exhibit excellent electrochemical performance.